"Breastfeeding" but not at the breast: Mothers' descriptions of providing pumped human milk to their infants via other containers and caregivers. Issue 3 (12th January 2017) - Felice, Julia P.; Geraghty, Sheela R.; Quaglieri, Caroline W.; Yamada, Rei; Wong, Adriana J.; Rasmussen, Kathleen M.
Abstract: As pumping has become more prevalent among American women, pumped human milk (HM) is on the rise in their infants' diets in place of some or all feeding at the breast. We aimed to fill a gap in knowledge about mothers' motivations, practices and perceptions related to pumping, and about mothers' and other caregivers' motivations, practices, and perceptions related to feeding pumped HM. Results related to providing pumped HM are reported here, and results related to pumping are reported elsewhere. We conducted in‐depth, semi‐structured interviews among a diverse sample of mothers whose infants were fed pumped HM ( n = 20), following each up to 1 year postpartum. Data were analyzed using thematic analysis with Atlas.ti. Nearly all mothers felt bottles were necessary to meet infant HM‐feeding goals. Nearly all pumped HM was fed by other caregivers because mothers typically preferred and prioritized feeding at the breast for convenience and maintaining their milk supply. Infants were bottle‐fed HM for several reasons that changed over time, such as mother's absence, latch difficulty, or desire to share the burden and bonding of feeding. Feeding practices differed between feeds from bottles versus at the breast; some infants were bottle‐fed on schedules but fed at the breast on demand. Mothers' methods for storing, transporting, and preparing HM varied substantially and included practices associated with loss of nutrients and microbial contamination. Mothers' reasons for bottle‐feeding HM may affect how much their infants are bottle‐fed. Consumption of pumped HM may not provide the same benefits to infants as feeding at the breast. These findings highlight important avenues for future research into the relationships between bottle‐feeding HM and infant health, growth, and developmental outcomes.